A wildfires vulnerability model for Guanacaste Conservation Area, Costa Rica (UNED Research Journal, 2018)
Wildfires occur in almost every type of ecosystem. However, vulnerability and propagation capacity of wildfires mostly relies on the amount of biomass and their water content. Particularly, Tropical dry forests are a vulnerable ecosystem to wildfires because, have at least six months with a precipitation of less than ten mm per month. Vulnerability assessment is a critical tool on wildfires management, defining the most vulnerable areas within the conservation area.The objective of this study was the implementation of a wildfire vulnerability model to identify priority areas for control and management of fire at Guanacaste Conservation Area (ACG). This model was designed integrating ecological components such as visual quality and biodiversity; and socio-economic components such as infrastructure and ecosystems services provided by ACG. Our results indicated that the most vulnerable areas at ACG contains a high density of species with pivotal ecological roles on ecosystem services. On the other hand, the less vulnerable areas are close to roads and communities. However, those last frequently experience wildfires. We expect that this model can be adapted in other protected wild areas with similar ecological and socio-economic characteristics to ACG and are often affected by wildfires taking into consideration the particularities present in each site.
Keywords: vulnerability; wildfires; tropical dry forest; risk; geographic information systems; Guanacaste Conservation Area.